GRF analysis of two elite paralympic sprinters in steady and resisted accelerated treadmill running - Breban, S. G.; Bettella, F.; Di Marco, R.; Migliore, G. L.; Cutti, A. G.; Petrone, N. (ISBS Proceedings Archive (Michigan), 2022)
Analysis of ground reaction forces (GRFs) allows evaluating performances of paralympic runners with transfemoral amputation. Instrumented treadmills are expensive and low-cost solutions to gather GRFs are worth to be studied. This study aimed to use a commercial treadmill placed on four force platforms to evaluate vertical impulse, braking and propulsive horizontal impulses during steady-speed (SSR) and resisted accelerated (RAR) running. The RAR vertical impulses of the unaffected limb (UL) of the two athletes doubled the values of the affected limb (AL) that has, however, on average 23% larger propulsive action than UL in SSR. The horizontal impulse of AL remains positive in the first 10 steps during RAR, as expected. Agreement between present results and literature confirms that the proposed setup gives sufficient confidence in the evaluation of the sprint technique.